2022
DOI: 10.3389/fmars.2022.923494
|View full text |Cite
|
Sign up to set email alerts
|

Contaminant Characteristics and Influencing Factors of Heavy Metals in Seawater and Sediments in a Typical Mariculture Bay in South China

Abstract: Heavy metal pollution in the mariculture areas is of considerable attention due to its potential ecological effects and public concern for seafood safety. A better understanding of the current contamination status and historical trend of heavy metals in the ecosystems of mariculture areas has an important implication for the sustainable development of marine ecosystems and for public health concerns. To assess the impact of human activities on heavy metal pollution in the mariculture area, seven metals (Cu, Pb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 65 publications
2
25
0
Order By: Relevance
“…Transport of the water masses is an important contribution to nutrient, primary productivity, phytoplankton and zooplankton community abundance in locally mixed seawater (Churchill et al, 2005;Gaughan et al, 2009;Kusum et al, 2019). Thus, nutrients and other materials in the BG are influenced not only by terrestrial pollution from coastal cities (Lao, Su et al, 2019;Lao et al, 2021Lao et al, , 2022 but also by pollution sources from other areas that enter the gulf with the transport of the water masses, such as the coast of western Guangdong (Chen, Dong, et al, 2019). Based on the proportional contribution of different water masses and nutrient concentrations in each water mass, the proportion of nutrient inputs into the BG with water masses can be quantified.…”
Section: Intrusion Of Water Masses Providing External Nutrients In Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…Transport of the water masses is an important contribution to nutrient, primary productivity, phytoplankton and zooplankton community abundance in locally mixed seawater (Churchill et al, 2005;Gaughan et al, 2009;Kusum et al, 2019). Thus, nutrients and other materials in the BG are influenced not only by terrestrial pollution from coastal cities (Lao, Su et al, 2019;Lao et al, 2021Lao et al, , 2022 but also by pollution sources from other areas that enter the gulf with the transport of the water masses, such as the coast of western Guangdong (Chen, Dong, et al, 2019). Based on the proportional contribution of different water masses and nutrient concentrations in each water mass, the proportion of nutrient inputs into the BG with water masses can be quantified.…”
Section: Intrusion Of Water Masses Providing External Nutrients In Th...mentioning
confidence: 99%
“…This indicated that water in the BG was considerably affected by WGCC intrusion. During winter, the runoff input into the BG decreases remarkably (Lao et al, 2020(Lao et al, , 2022, and water in the BG is evenly mixed. It forms an anti-clockwise circulation under the influence of the northeastern monsoon, with saline water intruding northward from the southern bay mouth and eastern QS (Xia et al, 2001).…”
Section: Seasonal Variation In Water Mass Processes In the Bgmentioning
confidence: 99%
“…Particularly in the marine environment, with the rapid economic and social development, large quantities of anthropogenic sources of heavy metals are discharged into the coastal environment, and those metals can be bioaccumulated by the marine organisms and biomagnified through the food chain, and ultimately endanger human health (Rainbow and Luoma, 2011;Kumar et al, 2019;Lao et al, 2019a;Liu et al, 2020;Huang et al, 2021). Thus, a better understanding of the current status of heavy metal contamination in marine ecosystems has a significant implication for the sustainable development of marine ecosystems, the seafood industry, and public concerns (Wang et al, 2013;Zhu and Zheng, 2017a;Zhu and Zheng, 2017b;Zhu and Zheng, 2018;Liu et al, 2020;Lao et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…Many researches have been increasingly concerned about the heavy metals in the marine environment. For example, increasing anthropogenic inputs of heavy metals into the seawater of mariculture areas have been reported due to the continuous expansion of the mariculture scale for the past decades (Wang et al, 2019;Liu et al, 2020;Lao et al, 2022a;Mohsen et al, 2022). Moreover, the coastal currents play an important role on the distribution of materials, and greatly impact on the local marine environment (Dong et al, 2012;Li et al, 2018;Lv et al, 2021;Hu et al, 2022;Lao et al, 2022b;Lao et al, 2022c).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation